Pengaruh Brand Image dan Word of Mouth Communication pada Keputusan Pembelian Smartphone Apple Iphone di Bandar Lampung - Natakusuma, Irwan; Kurniawan, Umarudin (Jurnal Enterpreneur dan Bisnis (JEBI), 2020)
The era of globalization impact on the development of modern communication technology and increasingly sophisticated so now to communicate does not have to communicate face-to-face (Face to face), because most forms of communication have been done in an indirect way, ie through the media / telecom tools such as using phone, email, chat, or by use of the media and skype video call. One of the telecom equipment available today is the smartphone. Smartphone or smart phone. One of the smartphone brand in demand by today’s society is the Apple Iphone.